Extreme precipitation events over north China in August 2010 and their link to eastward‐propagating wave‐trains across Eurasia: observations and monthly forecasting. (1st September 2015) - Orsolini, Yvan J.; Zhang, Ling; Peters, Dieter H. W.; Fraedrich, Klaus; Zhu, Xiuhua; Schneidereit, Andrea; van den Hurk, Bart
Abstract : Over the Far East in summer, climate is strongly influenced by the fluctuating Western Pacific Subtropical High (WPSH), and strong precipitation is often associated with southeasterly low‐level wind that brings moist air from the southern China seas. The WPSH intraseasonal variability is partly influenced by quasi‐stationary wave‐trains propagating eastwards from Europe across Asia along the two westerly jets: the Silk‐Road wave‐train along the Asian jet at midlatitudes and the polar wave‐train along the sub‐polar jet. In the unusual summer of 2010, northeast China experienced its worst seasonal flooding for a decade, triggered by unusually severe precipitation. That summer was also characterized by a record‐breaking heat wave over eastern Europe and Russia, whose impact on the precipitation further east over China has been little explored. Here, we examine the role of the Silk‐Road and polar wave‐trains, and their impact on precipitation over northeast China throughout August 2010, using station precipitation data and re‐analyses. We found that there is a strong link between the Silk‐Road wave‐train and extreme precipitation events. Forecasting such regional precipitation events at the monthly time‐scale remains a big challenge for operational global prediction systems. In this study, we use simulations with the atmospheric model of the European Centre for Medium‐range Weather Forecasts (ECMWF) to highlight the key role of the Silk‐Road and polar wave‐trains in modulating extreme precipitation over north and northeast China in August 2010. While the ensemble‐mean of the forecasts fails to predict the pulses of the Silk‐Road wave‐train, some model members show a high spatial correlation in upper‐level meridional winds with re‐analyses. Similarly, there is high spatial correlation between model meridional winds and precipitation. These results highlight the importance of better representing the intraseasonal evolution of the Silk‐Road wave‐train in order to improve the monthly prediction of summer precipitation over the Far East.